Evaluation of anxiety and depression among medical students using duke health profile - Warsi, Umaima; Shafqat, Tehreem; Hameed, Sehrish (International Journal of Endorsing Health Science Research, 2017)
Background: Depression is an important health problem due to its prevalence and associated consequences. The life time prevalence of depression ranges between 10 to 21 % in population. According to the precipitation of the WHO, depression is estimated to become the second leading cause of dysfunction by the year 2020. Among medical students, academic stressors include the volume of material to be learned, academic performance and evaluation (examinations and continuous assessments). Method: A cross-sectional study was conducted and the total of 300 Medical students from 18 to 25 years to age participated in this study. Students in this study were undergraduate students. Duke health profile were given to the students. Data analysis was done by using Chi square test. Results: 300 students from fourth year and final year were recruited for the study. Mean anxiety score was 35.4 SD + 19.9 with minimum score of 0 and maximum score of 99.6. Mean depression score was 35.9 SD + 21.8 with minimum score of 0 and maximum score of 100. Mean anxiety depression score was 28.8 SD + 33.8 with minimum score of 0 and maximum score of 100. Mental score was compared among medical students, 47.4% of fourth years and 34.2% of had severe mental stress (Score 75 – 100), Anxiety score was compared among medical students, 2.6% of fourth years and 3.4% of had severe anxiety (Score 75 – 100), Depression score was compared among medical students, 3.9% of fourth years and 5.5% of had severe depression (Score 75 – 100), 14.9% of fourth years and 18.5% of had moderate depression (Score 50 – 75). Conclusion: Anxiety score showed a little female predominance. Depression among medical students of fourth year was little more as compared to the final year students. Depression was more among male students than female students.